Potential Commodity Based Fishing Technology Development in Lampung Bay - Tri Hariyanto; Mulyono S Baskoro; John Haluan; Budhi H Iskandar (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2008)
Lampung Bay and the adjacent water bodies, Northern Sunda Strait, Western Java Sea, is a potential area for fish capture armada which based in South Lampung Coast. Not all the areas have maximum potency since there is inadequacy for fish capture technical armada and seasonal environment dynamic. This investigation identified fisheries resources on Lampung Bay and fishing gear and potential commodities to developed. This identification implemented by analyzing the provided data to obtain the illustration of Catch Per Unit Effort (CPUE) in the Lampung Bay area. Fish capture at the Lampung Bay has been shown the indication of production decline. Therefore, the attempt of capture organizing at the Lampung Bay and the improving of fisherman competence and armada to capture at the Lampung Bay water bodies or Indian Ocean (reach ZEE) should be conducted. Selective fishing gear for catch the potential commodities applied at the Lampung Bay areas. Keywords: Lampung bay, fisheries management, CPUE.